Predicting women's intentions for contralateral prophylactic mastectomy: An application of an extended theory of planned behaviour. (April 2016) - Richards, Imogen; Tesson, Stephanie; Porter, David; Phillips, Kelly-Anne; Rankin, Nicole; Musiello, Toni; Marven, Michelle; Butow, Phyllis
Abstract: Purpose: Most women with unilateral breast cancer (BC) without BRCA1/2 gene mutations are at low risk of contralateral breast cancer (CBC). One CBC risk-management option is contralateral prophylactic mastectomy (CPM). While there is no evidence that CPM increases life-expectancy, its uptake is increasing. This study aimed to assess the validity of an extended social-cognition model, the Theory of Planned Behaviour (TPB), in predicting women's intentions to undergo CPM. Method: Four hundred women previously treated for BC completed an online survey exploring demographic and disease factors, attitude, subjective norm, perceived behavioural control, anticipated regret, uncertainty avoidance, self-efficacy to not have CPM and intentions to undergo CPM in a common hypothetical decision-making scenario. Results: The TPB uniquely explained 25.7% of intention variance. Greater anticipated regret, uncertainty avoidance and lower self-efficacy to cope with not having CPM were associated with stronger CPM intentions, explaining an additional 7.7%, 10.6% and 2.9% respectively, of variance over and above the TPB. Women who had undergone CPM, had not attended university, and had children reported stronger CPM intentions. Conclusions: A holistic understanding of CPM decision-making appears to require consideration beyond CBC risk, demographics and disease characteristics, exploring women's expectations about CPM outcomes, others' opinions, and avoidance of emotionality and difficulties associated with not undergoing surgery. This study provides a theoretical basis from which the complexity of CPM decision-making may be understood, and from which resources for patients and treating staff may be developed to support women's informed decision-making aligning with their personal values. Highlights: CPM decision-making is influenced by women's beliefs about CPM and their social environment. Avoidance of negative affect and difficulties linked to not having surgery impact on CPM intentions. The results provide strong support for the development of a decision-aid for CPM decision making.